Influence of Hydroxyapatite Nanospheres in Dentin Adhesive on the Dentin Bond Integrity and Degree of Conversion: A Scanning Electron Microscopy (SEM), Raman, Fourier Transform-Infrared (FTIR), and Microtensile Study - Al-Hamdan, Rana S (Polymers (Basel), 2020)
An experimental adhesive incorporated with different nano-hydroxyapatite (n-HA) particle concentrations was synthesized and analyzed for dentin interaction, micro-tensile bond strength (μTBS), and degree of conversion (DC). n-HA powder (5 wt % and 10 wt %) were added in adhesive to yield three groups; gp-1: control experimental adhesive (CEA, 0 wt % HA), gp-2: 5 wt % n-HA (HAA-5%), and gp-3: 10 wt % n-HA (HAA-10%). The morphology of n-HA spheres was evaluated using Scanning Electron Microscopy (SEM). Their interaction in the adhesives was identified with SEM, Energy-Dispersive X-ray (EDX), and Micro-Raman spectroscopy. Teeth were sectioned, divided in study groups, and assessed for μTBS and failure mode. Employing Fourier Transform-Infrared (FTIR) spectroscopy, the DC of the adhesives was assessed. EDX mapping revealed the occurrence of oxygen, calcium, and phosphorus in the HAA-5% and HAA-10% groups. HAA-5% had the greatest μTBS values followed by HAA-10%. The presence of apatite was shown by FTIR spectra and Micro-Raman demonstrated phosphate and carbonate groups for n-HA spheres. The highest DC was observed for the CEA group followed by HAA-5%. n-HA spheres exhibited dentin interaction and formed a hybrid layer with resin tags. HAA-5% demonstrated superior μTBS compared with HAA-10% and control adhesive. The DC for HAA-5% was comparable to control adhesive.